Pemodelan Efisiensi Energi Panel Surya Berdasarkan Variasi Suhu Dengan Algoritma Random Forest (Jurnal Ampere, 2024)
When temperature increases, energy efficiency tends to decrease. This is because the materials in solar panels, especially photovoltaic cells, have characteristics that make them less efficient at converting solar energy into electrical energy when temperatures rise. By using the random forest research method and Rstudio software to help analyze it can be concluded that the temperature variation that has the most influence on power efficiency is light intensity with a contribution of 19%, then air temperature with 18%, humidity with 17.5%, wind speed with 14%. 5% and finally panel temperature with a contribution of 13%. This contribution is the contribution to the power produced by the effect of temperature on the power produced. at 10.13 the highest power was obtained, where the power produced was 164.48 Watts. With a light intensity of 431.44 cd (candela), air temperature of 41.9°C, humidity of 49.4%, wind speed of 0.2 m/s, and panel temperature of 35 °C